MULTIPLE NEGATION IN CORPUS AND DISCOURSE - Bekhta, Ivan; Tatarovska , Olesya (Philological Treatises, 2023)
The relevance of the chosen topic is substantiated, research tasks and methods are formulated, literary sources of analysis are indicated, and the compositional structure of the article is outlined. A brief overview of the theoretical material and a working definition of the linguistic category of negation are presented, the main terms are defined, and the main approaches to the interpretation of the category of negation are defined in domestic and foreign sources. The objection is considered in the views of scientists of various fields of linguistics. Attention is drawn to the historical issues of language development, namely: the use of multiple negation and its separate subtypes in different periods of the English language. The specifics and pragma-functional features of the speech of British youth are determined. Emphasis is placed on the psychological and linguistic (discourse) development of adolescents. Part of the article is devoted to the level analysis of systemic means of negation in terms of their functioning in the text. The pragmatic character of units-components of negative intensification is described. Along with the main laws, narrower points are also involved: presented, analyzed and divided into classes and semantic subcategories and idioms with negative polarity in modern English. The focus of the article is the context as an independent object of observation, which proves the undeniable pragmatic motivation of negation in modern English writing and speech. The results of the research are summarized, the main characteristics of which are the establishment of functional equality of all means of negation at each language level, in the text and in speech; and also - in revealing their unlimited possibilities for the transfer of negative information of the most varied volume.